The Age of Aquarius – an era of true liberation from enslavement (from a society of isolation and fragmentation to a society of coexistence and integration) - Karibe, Yoshihito (Journal of the Belarusian State University. Sociology, 2026)
The importance of a person’s consciousness as a member of society is noted. It is rightly pointed out that the current system fosters narrow-minded selfishness, a focus on ruthless competition for limited resources, and a disregard for the interests of others and society as a whole, which are the root causes of most of the crises in the modern world. The article predicts a global catastrophe as the logical and most likely outcome of this development model and emphasises the need for a paradigm shift to preserve humanity’s future. The importance of educating individuals based on humanistic and altruistic ideals is highlighted.
Keywords: spiritual freedom; materialism; idealism; egoism; consciousness; karma (karmic causality); alaya-vijnana; spiritual enlightenment; humanism; civilisational paradigm shift